Is one the loneliest number? Impact of tourists' ability to identify individual bears on conservation outcomes - Skibins, Jeffrey C.; Richardson, Leslie; Lewis, Lynne; Fitz, Mike (Frontiers in Sustainable Tourism, 2023)
Introduction A fundamental component of ecotourism is resource conservation. Oftentimes, that resource is wildlife. Within the wildlife-centric ecotourism experience, tourists' encounters are most often with individual animals, or a small subset of the population (i.e., not the species as a whole). However, most conservation efforts are focused at the species level. This article explores the relationship between tourists' ability to identify individual animals and conservation outcomes. Methods Data were obtained from 3,853 online surveys from viewers of the Katmai National Park and Preserve webcams (bearcams). Results The majority of respondents (70%) indicated they could identify individual bears. Respondents who could identify individual bears had significantly higher scores for conservation outcomes (i.e., awareness, behavioral intention, and emotional connection). Furthermore, identifying an individual bear as a favorite yielded significantly higher scores for emotional connectivity and support for conservation programs. Discussion Thus, the ability to identify individual animals, when viewing wildlife, can improve conservation outcomes. Practitioners could consider incorporating strategies to improve tourists' identification skills as a method to cultivating conservation outcomes.